(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To determine the incidence of thyroid dysfunction in infertile women and comment on some factors related to thyroid dysfunction in infertile women. Subjects and methods: A cross-sectional study on 473 infertile women examined in the National Obstetrics and Gynecology Hospital who were tested FT4, TSH. Relevant factors to be investigated included age, BMI, histories of miscarriage or stillbirth, blood prolactin levels and AMH. Thyroid dysfunction was assessed based on TSH levels above or below the normal reference range (TSH: 0.45 - 4.12) according to ATA 2012. Results: The rate of thyroid dysfunction in the study patient group was 13,32%. The incidence of hypothyroidism was 7,82%, including 4,5% subclinical hypothyroidism and 2,32% of clinical hypothyroidism. The incidence of hyperthyroidism was 5,49%, including 3,59% of subclinical hyperthyroidism; 1,90% of clinical hyperthyroidism. The incidence of thyroid dysfunction was higher in the group of older women and more frequent in the group over 35 years old. The proportion of patients with stillbirth, miscarriage histories in hyperthyroidism group was 26,92%; in the hypothyroidism group was 27,03%. The rate of hyperprolactinemia in the hypothyroidism group (27,02%) higher than the euthyroid group (12,87%). Patients with AMH level < 2 ng/ml in the hyperthyroidism group (48%) and hypothyroidism group (54,04%) are higher than the euthyroid group (36,37%). Conclusion: The rate of thyroid dysfunction of infertile women in the study was 13.32%; higher in the age group over 35. The proportion of miscarriage, stillbirth hyperprolactinemia or AMH concentration < 2 ng/ml was higher in the thyroid disorder group than the euthyroid group.